Application of Blood Oxygenation Level–Dependent Magnetic Resonance Imaging and Intravoxel Incoherent Motion to Assess Bilateral Renal Pathophysiological Processes Induced by Iodixanol Renal Artery First-Pass in Rabbit Model. Issue 4 (July 2019) - Wang, Zhiqiang; Ren, Ke
Abstract : Background: Noninvasive blood oxygen level–dependent imaging and intravoxel incoherent motion sequences were used to assess bilateral renal oxygenation, hemodynamics, and proton diffusion in iodixanol renal artery first-pass in rabbit model. Methods: Forty-two rabbits were divided into 2 groups. Saline and iodixanol (1 g iodine/kg, left renal artery) were administered. Magnetic resonance imaging scans were acquired longitudinally at 24 hours prior to and 1, 24, 48, and 72 hours after administration to assess apparent diffusion coefficient, pure molecular diffusion ( D ), perfusion-related diffusion ( D *), volume fraction ( f ), and relative spin-spin relaxation rate (R2*) values, respectively. The experiment evaluated serum creatinine, histological, and hypoxia-inducible factor 1α immunoexpression. Results: During 1 to 48 hours, the values of D, f, and D * significantly decreased ( P < 0.05), but R2* values significantly increased ( P < 0.05) in cortex, outer medulla, and inner medulla after administration of iodixanol through left renal artery, which showed in the 72 hours. The change of the left kidney is noteworthy. Significant negative correlations were observed between apparent diffusion coefficient, D, f, and R2* in cortex, outer medulla, and inner medulla (all P < 0.001, r = −0.635–0.697). Conclusions: The first-pass effect of the contrast agent significantly reduces ipsilateral renal perfusion and renal oxygenation, and noninvasive monitoring can be performed by using blood oxygen level–dependent magnetic resonance imaging and intravoxel incoherent motion.